2018
DOI: 10.3389/fenvs.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Process Steps of Pretreatment, Pellet Production and Combustion for an Energetic Utilization of Wheat Chaff

Abstract: This paper investigates the potential energetic utilization of wheat chaff via combustion and necessary process steps such as pretreatment and pellet production as an example of stramineous biomass. Chaff is one out of three main fractions during harvesting and remains usually on the field. Vice versa, it is a potentially so far unexploited biomass resource, which could serve as renewable energy source. Simultaneously, exploiting wheat chaff could intensify the economic benefit of agricultural land use. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Prior research in the Sweedhart project investigated the densification of chaff via pelleting successfully and defined important conditions for the pelleting process [26].…”
Section: Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research in the Sweedhart project investigated the densification of chaff via pelleting successfully and defined important conditions for the pelleting process [26].…”
Section: Conditioningmentioning
confidence: 99%
“…A pellet press can process fibers between 3.2 and 6.4 mm [34]. Therefore, a reduction in size is necessary, before feeding chaff into the press [26]. In biomass pelleting plants, hammer mills are commonly used for grinding [25].…”
Section: Conditioningmentioning
confidence: 99%
“…However, although a relationship between the amount of residue maintained on the soil and the soil organic matter (SOM) was found in previous studies [14,15]. due to the low nutrient content in cobs and wheat chaff, their removal is considered unlikely to affect soil fertility [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the EU-28 produced yearly 152 Mt wheat and spelt [6], and chaff, a heterogeneous mixture of glumes, dust, short straw pieces, broken grain seeds, and weed seeds represents a potential biomass of 38 Mt year −1 . Considering the lowest heating value of chaff of 15.1 MJ kg −1 [7], and the removal rate of 0.33, for a stable soil balance [8], it is possible to estimate a theoretical energy availability of 191 PJ year −1 [9]. In EU-28 more than 9 Mha of grain maize are cultivated yearly [10].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion experiments of chaff showed that sorting of chaff before compressing can be beneficial for the handling and the combustion application. Furthermore, chaff can be compressed to briquettes or pellets to ease the handling, lower the transport costs and to decrease the storage volume of chaff [37]. Collecting chaff directly during the harvest in a trailer has the advantage that all weed seeds in the chaff fraction are assembled together with the chaff.…”
Section: Field Experiments With Wheat Chaffmentioning
confidence: 99%